Pengaruh Kepemilikan Instiusional, Kepemilikan Manajerial, Return On Assets (ROA) Dan Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility (CSR) (Studi pada perusahaan manufaktur sub sektor property & real estate yang terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Nanda Sasqia Zahro; Achmad Agus Prioyono; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the impact of Institutional Ownership, Managerial Ownership, ROA and Company Size on CSR disclosure in Property & Real Estate manufacturing sub-sector companies listed on the IDX in 2017-2019. The data analysis method used multiple linear regression analysis. The population of this study is the property & real estate manufacturing sub-sector companies listed on the IDX in 2017-2019, which are 65 companies. In this study, the sample selection used purposive sampling technique, in order to obtain 14 companies that matched the criteria in the property & real estate manufacturing sub-sector companies. The results of this study indicate that simultaneously institutional ownership, managerial ownership, return on assets (ROA) and firm size have no effect on CSR disclosure. Partially shows that (1) Institutional Ownership has a positive and insignificant effect on CSR disclosure, (2) Managerial Ownership has a negative and insignificant effect on CSR disclosure, (3) Return on Assets (ROA) has a negative and insignificant effect on CSR disclosure, (4) Firm size has a positive and insignificant effect on CSR disclosure. Keywords: Institutional Ownership, Managerial Ownership, Return On Assets (ROA), Company Size, Corporate Social Responsibility (CSR).